Religious diversity in America - Rodriquez, Carlo; McWhirter, Shannon; Educational Video Network, Inc. (Huntsville, Tex. : Educational Video Network, 2002)
In America there are a variety of cultures that are defined by many different religions. Discover the elements of Judaism, Islam, Christianity, Hinduism, and Buddhism; learn about these beliefs and the systems that guide them.
Belief systems -- General religious terms -- Judaism: terms & definitions -- Islam: terms & definitions -- Christianity: terms & definitions -- Hinduism: terms & definitions -- Buddhism: terms & definitions.
Laura Berryhill, narrator.
VHS.
Keywords: Religion; Cultural pluralism